2017
DOI: 10.1007/s12079-017-0389-3
|View full text |Cite
|
Sign up to set email alerts
|

EGFR signaling pathways are wired differently in normal 184A1L5 human mammary epithelial and MDA-MB-231 breast cancer cells

Abstract: Because of differences in the downstream signaling patterns of its pathways, the role of the human epidermal growth factor family of receptors (HER) in promoting cell growth and survival is cell line and context dependent. Using two model cell lines, we have studied how the regulatory interaction network among the key proteins of HER signaling pathways may be rewired upon normal to cancerous transformation. We in particular investigated how the transcription factor STAT3 and several key kinases' involvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Researchers have demonstrated that ERK/p38/JNK pathway involves the regulation of the proliferation, differentiation, apoptosis and metastasis of various cancer cells (23,24,28,29). Wang et al confirmed that miR-155 increases OS cell growth by regulating MAPK signaling (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that ERK/p38/JNK pathway involves the regulation of the proliferation, differentiation, apoptosis and metastasis of various cancer cells (23,24,28,29). Wang et al confirmed that miR-155 increases OS cell growth by regulating MAPK signaling (59).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that MAPKs exist in the majority of cells, and are associated with the proliferation, differentiation and apoptosis of various cells (25-27). Three different MAPK signaling pathways, including p38 MAPK, c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK) (28,29), have been found in mammals. A number of studies have confirmed that these 3 signals can regulate the progression of various types of tumors, for example, OS, prostate cancer and glioma (30-32).…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem of network reconstruction from experimental data remains a challenging task, for which many different approaches have been suggested. Among those, Modular Response Analysis (MRA) has been proven successful in many applications 1 4 . MRA uses steady-state data of experiments in which each node of a network is perturbed successively (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 protein expression and phosphorylation at tyrosine (Y705) and serine (S727) sites were measured using western blots [ 18 ]. Briefly cells at 75% confluency were lysed using RIPA buffer with protease and phosphatase inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were developed using chemiluminescence ECL reagent (Thermofisher Scientific, cat # 34095). Western blot images were captured with a LI-COR C-Digit scanner and protein band intensities were measured and analysed using LI-COR Image Studio Digits v3.1 software [ 18 ].…”
Section: Methodsmentioning
confidence: 99%